2011
DOI: 10.1007/s11483-011-9232-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Characterization of Casein Micelles Under NaCl Range Conditions

Abstract: Micellar casein (MC) dispersions were studied at a constant protein concentration of 5 wt % in high NaCl environment. The micellar edifices were characterized as to their morphology, size, and content of proteins in the supernatant after ultracentrifugation. Additionally, changes in secondary structures of the protein upon salt increase were followed by Fourier Transform Infrared Spectroscopy (FTIR). For the first time, the estimations of secondary structural elements (irregular, ß-sheet, α-helix and turn) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 58 publications
2
33
0
1
Order By: Relevance
“…The spectroscopy of FTIR were obtained with a VERTEX 70V Bruker spectrometer (Bruker Corporation, Karlsruhe, Germany) equipped with an ATR cell (Total Attenuated Reflection mode) and a MCT (Mercury Cadmium Telluride) detector cooled with liquid N 2 as described by Hussain, Gaiani, Aberkane, Ghanbaja, and Scher (2011).…”
Section: Ftir Spectroscopymentioning
confidence: 99%
See 3 more Smart Citations
“…The spectroscopy of FTIR were obtained with a VERTEX 70V Bruker spectrometer (Bruker Corporation, Karlsruhe, Germany) equipped with an ATR cell (Total Attenuated Reflection mode) and a MCT (Mercury Cadmium Telluride) detector cooled with liquid N 2 as described by Hussain, Gaiani, Aberkane, Ghanbaja, and Scher (2011).…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…Peak assignment of Amide I region was performed using the results of former studies for caseins (Hussain et al, 2011). During the iteration process the peaks positions were allowed to shift which was less than 2 cm À1 .…”
Section: Ftir Spectra Of Yak Casein Micellesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it has been reported that adding sodium chloride in this step increases the yield (Locci et al 2012). Sodium chloride is reported to change the conformation of casein proteins (Hussain et al 2011) and modify the solubility of the different casein fractions (Post et al 2012). Since cheese is a soft gel of concentrated casein micelles with embedded fat globules and a continuous serum phase, the swelling of this concentrated protein network increases in the presence of sodium chloride (de Kruif et al 2015;Guo et al 1997).…”
Section: Introductionmentioning
confidence: 99%